Testing Practices in European Countries - Muniz, Jose; Bartram, Dave; Evers, Arne Boben, Dušica; Matešić, Krunoslav Glabeke, Kathia; Fernandez-Hermida, Jose R. Zaal, Jac N (2001)
Tests constitute one of the technological tools most frequently used by psychologists in their professional practice. Like any other scientific technology, tests can be used both in appropriate and inappropriate ways. Currently, various institutions, both national and international, are developing projects and activities aimed at improving testing practices. In Europe, the Task Force on Tests and Testing created by the European Federation of Professional Psychologists+ Associations (EFPPA) designed a questionnaire to sample the opinions of professional psychologists about tests and testing in order to help in making the right decisions for improving testing practices in Europe. This paper presents the results obtained using the EFPPA Questionnaire. A sample of 3, 455 Spanish, 2, 407 English, 2, 079 Dutch, 321 Slovenian, 218 Croatian and 210 Belgian psychologists responded to the questionnaire. In general, European psychologists show a positive attitude toward tests and testing, while at the same time expressing the need for institutions to adopt a more active role in promoting tood testing practices. Results show that the tests most frequently used are intelligence tests, personality questionnaires and depression scales. Finally, the results are analyzed in detail, and some possible measures for improving testing practices in Europe are discussed.
ENG